2016
DOI: 10.1016/j.apsoil.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and validating predictions of soil bacterial biodiversity using European and national scale datasets

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Recent research has highlighted strong correlations between soil edaphic parameters 24 and bacterial biodiversity. Here we seek to explore these relationships across the European 25 Mapping and validating predictions of bacterial biodiversity using European andUnion member states with respect to mapping bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 26 publications
(28 reference statements)
6
42
0
Order By: Relevance
“…Another soil property that can play an important and significant role on C dynamics is pH; varying from each sampling areas and affecting soil reduction and oxidation processes into the soil can determine the fate of C substrate addressing to accumulation or mineralization [72] and vice versa. Indeed, in our soil survey, C accumulation in acid and sub-acid soil (OM, OF, CT, NAT) was higher than under neutral pH (ACI, ACR, V), thus confirming the negative correlation between soil pH and TOC content, as also observed by other authors [73], who related higher pH values to higher microbial mineralization activity. Soil pH, furthermore, is an important factor revealing TIC distribution across land uses and soil acidification processes [5].…”
Section: Main Factors Affecting C Accumulationsupporting
confidence: 92%
“…Another soil property that can play an important and significant role on C dynamics is pH; varying from each sampling areas and affecting soil reduction and oxidation processes into the soil can determine the fate of C substrate addressing to accumulation or mineralization [72] and vice versa. Indeed, in our soil survey, C accumulation in acid and sub-acid soil (OM, OF, CT, NAT) was higher than under neutral pH (ACI, ACR, V), thus confirming the negative correlation between soil pH and TOC content, as also observed by other authors [73], who related higher pH values to higher microbial mineralization activity. Soil pH, furthermore, is an important factor revealing TIC distribution across land uses and soil acidification processes [5].…”
Section: Main Factors Affecting C Accumulationsupporting
confidence: 92%
“…The results in Fig 5c show that the observed and predicted first axis ordination scores were highly related ( r 2 = 0.88) demonstrating that it is possible to predict broad scale community change from individual OTU relative abundance pH models. These findings add to a growing body of literature on the predictability of soil bacterial communities 3335 ; but furthermore demonstrate the utility of our overall approach in deriving meaningful ecological information from matches to a 16S rRNA sequence database incorporating ecological responses.…”
Section: Resultssupporting
confidence: 52%
“…As proof of the two concepts, we produced two maps of the soil biodiversity and habitat function of soils, one for the Netherlands and one for Europe. This work in progress is a follow up of earlier publications on a regional scale (e.g., Scotland [34], France [35,36], Netherlands [29]), and European scale (e.g., [20,21,30,32,37]). We took advantage of the progress of the monitoring of soil biological attributes in the Netherlands [11] and in many EU-projects, i.e., SoilTrec [38], Soilservice [16], EcoFINDERS [17,33], and LANDMARK [9].…”
Section: Introductionmentioning
confidence: 69%
“…The pilot contained samples from forestry, arable, and grassland systems in five climatic zones of Europe. Griffiths et al (2016) [20] found a strong correlation between soil pH and bacterial diversity (TRFLP analysis) in these samples, and produced a bacterial diversity map of Europe. Earthworms were excluded from the monitoring for logistical reasons [33], but [21] instead collected and harmonized existing earthworm data from 3838 sites in several European countries and applied digital soil mapping in order to produce a European map with earthworm community parameters, i.e., abundance, richness, and Shannon-Wiener index.…”
Section: Introductionmentioning
confidence: 89%